Rhachidelus Brazili Boulenger, 1908 (Squamata: Serpentes: Dipsadidae): New records, range extension and distribution map in mato grosso and mato grosso do Sul states, Brazil - Arruda, Luana A.G.; Ávila, Robson W.; Morais, Drausio H. [UNESP]; Kawashita-Ribeiro, Ricardo A. (My University, 2011)
The present study reports new records of the Dipsadid snake Rhachidelus brazili Boulenger, 1908, from Mato Grosso and Mato Grosso do Sul states, Brazil. Our data extend the known geographical distribution ca. 713 km to the northwest and constitute the first record in the Upper Paraguay sub-basin. © 2011 Check List and Authors.